2010
DOI: 10.1590/s0102-311x2010000500015
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência de diabetes mellitus e identificação de fatores associados em adultos residentes em área urbana de Ribeirão Preto, São Paulo, Brasil, 2006: Projeto OBEDIARP

Abstract: Para investigar a prevalência de diabetes mellitus e fatores associados, conduziu-se estudo epidemiológico transversal em amostra de adultos com 30 anos e mais, residentes em Ribeirão Preto, São Paulo, Brasil. O processo de amostragem foi desenvolvido em três estágios e pesos amostrais foram calculados, obtendo-se amostra ponderada de 2.197 participantes. Para o diagnóstico de diabetes mellitus considerou-se história prévia e pontos de corte recomendados pela Organização Mundial da Saúde (OMS) para glicemias d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1
64

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(88 citation statements)
references
References 29 publications
3
20
1
64
Order By: Relevance
“…The observed prevalence of DM2 (13.7%) was higher than the values detected in the Multicenter Study of the Prevalence of Diabetes Mellitus in Brazil (4), 7.6% for the national mean and 9.6% for the city of São Paulo (9.6%), and was comparable to the 12.1% prevalence detected in the adult population aged 30 to 69 years in a study conducted in Ribeirão Preto, SP, 1997 (5). The observed prevalence of DM was of slightly lower values compared to data obtained in recent studies in Ribeirão Preto-SP (15.02%) and region (13.5%) (18,19). However, it differed from the 34.9% value observed in the second survey performed in 2000 in the Japanese-Brazilian population of Bauru, SP (9)(10)(11).…”
Section: Discussioncontrasting
confidence: 58%
“…The observed prevalence of DM2 (13.7%) was higher than the values detected in the Multicenter Study of the Prevalence of Diabetes Mellitus in Brazil (4), 7.6% for the national mean and 9.6% for the city of São Paulo (9.6%), and was comparable to the 12.1% prevalence detected in the adult population aged 30 to 69 years in a study conducted in Ribeirão Preto, SP, 1997 (5). The observed prevalence of DM was of slightly lower values compared to data obtained in recent studies in Ribeirão Preto-SP (15.02%) and region (13.5%) (18,19). However, it differed from the 34.9% value observed in the second survey performed in 2000 in the Japanese-Brazilian population of Bauru, SP (9)(10)(11).…”
Section: Discussioncontrasting
confidence: 58%
“…Difficulties to specify the evolution time of the disease were also found in a prevalence study in Ribeirão Preto-SP, which showed that 25% of subjects with DM did not know their diagnosis (25) . Another prevalence study, developed seven years later in the same city, detected that 15% of subjects did not know the diagnosis (24) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies appoint that, in the establishment of DM2 diagnoses, people already present some kind of complication (23)(24)(25) . Difficulties to exactly determine the duration of DM2 should be highlighted, due to the asymptomatic period preceding the diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, a population-based study carried out in the state capitals between [1986][1987][1988], with a population of 30-69 year olds, showed a prevalence of 7.6% for diabetes and, in the state of Sao Paulo, this was 9.7%. 12 More recent regional studies show higher rates; of 15.0% in the city of Ribeirao Preto, SP, Southeastern Brazil in 2005-2007, 14 and of 13.5%, in Sao Carlos, SP, in 2008. 4 With increased prevalence in the general population, it is possible that this increase is also occurring among pregnant women.…”
mentioning
confidence: 97%